Leadership Agility During the Covid-19 Pandemic Affected by Leadership Self-Efficacy and Trust in Team Members - Indah Rizki Maulia; Didit Rahardi (Budapest International Research and Critics University, 2022)
The purpose of this study was to determine whether there was an influence of leadership self-efficacy and trust in team members on leadership agility during the Covid-19 pandemic crisis. The research method used is correlational quantitative with survey method. A questionnaire in the form of an attitude scale was used as an instrument in this study. The research sample was selected using purposive sampling with the characteristics of those who occupy positions as leaders in the company. This study found that there was a significant effect of leadership self-efficacy and trust in team members on leadership agility during the Covid-19 pandemic crisis. Leadership self-efficacy and trust in team members simultaneously have an effect of 55.4% in Leadership Agility. Leadership self-efficacy has a significant and positive effect on leadership agility, while trust in team members has a significant and negative effect on leadership agility. Limitations in this study are the limited number of subjects who are willing to become research respondents and the limited mobility of researchers due to Indonesian government regulations regarding community activities during Covid-19 pandemic. The benefits of this research include increasing knowledge in the field of management science regarding leadership agility, leadership self-efficacy, and trust in team members. Another benefit is to provide information for organizations and leaders within the organization about the things needed by a leader to be agile, especially in times of crisis.